Penggunaan Website OJAD dan Tsutaeru Hatsuon Untuk Meningkatkan Kemampuan Pelafalan Bahasa Jepang Guru SMA di Jawa Tengah - Heni Hernawati; Dwi Puji Asrini; Yanuar Lutfi R (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Based on the preliminary study, it can be seen that the Japanese Language MGMP in Central Java is facing problems regarding the teaching of Japanese pronunciation. Many students pronounce Japanese incorrectly causing communication to not go smoothly. For example, when pronouncing the word ojiisan (おじいさん) which means “grandfather”, but pronounced with a short sound ojisan （おじさん）which means “uncle”. In addition, when pronouncing the word “ame” （雨）which means “rain” which should be pronounced with a high accent at the beginning, it is pronounced with “ame” （飴）with a high accent at the end, so the meaning changes to “candy”. Teachers have difficulty teaching it. To overcome the partner's problems, a workshop was held with the aim of providing knowledge about using the OJAD website and Tsutaeru Hatsuon. Through this workshop, high school Japanese teachers in Central Java can improve their ability to master and apply Japanese pronunciation, especially on Japanese accent, intonation and rhythm, then teach it to students.